Refractory hematuria post actinic cystitis. Role of potassium alumen as treatment - Case Report - Pinto Filho, João Ernesto Aldred; Ejje Kailly, Pedro Henrique; Louback Filho, Ruston da Matta; Renteria, Juan Miguel; Claudio, Antonio; Cunha, Ahouagi (Global Journal of Medical and Clinical Case Reports, 2022)
Actinic cystitis hematuria is a frequent complication after pelvic radiotherapy, present in approximately 5% of patients exposed to this therapy. The management of these cases seems to be a challenge for today’s urologists. In this article, we present the case of a 73- year-old man diagnosed with actinic cystitis after pelvic radiotherapy and admitted to our service with a clinical picture of refractory macroscopic hematuria. During admission, the patient underwent multiple procedures and blood transfusions, without success in controlling hematuria. After a review of the literature, we chose to use Potassium Alum in the patient’s treatment. Under general anesthesia, we performed a cystoscopy with the evacuation of clots and subsequently infused a 1% solution of potassium alum into the bladder at a rate of 200 ml/h for 25 hours. Less than 24 hours after Alum infusion, there were no more clinical signs of hematuria, which remained until hospital discharge. After 6 months of treatment, the patient did not present another episode of hematuria.